The Role of the Dıgıtal Economy ın the Development of Entrepreneurshıp ın a Market Economy - Ashraf Qurbonaliyevich Abdualimov; Ikrom Ural ugli Bakhtiyorov (Genius Journals, 2022)
This article discusses the development of entrepreneurship, which is the main link of the market economy, the role and importance of the modern digital information system, and its positive and negative aspects in the effective organization of business today.
Keywords: Economy; the market economy; business entity; small business